Fungal G-Protein-Coupled Receptors: A Promising Mediator of the Impact of Extracellular Signals on Biosynthesis of Ochratoxin A - Gao, Jing; Xu, Xinge; Huang, Kunlun; Liang, Zhihong (Frontiers in Microbiology, 2021)
G-protein-coupled receptors (GPCRs) are transmembrane receptors involved in transducing signals from the external environment inside the cell, which enables fungi to coordinate cell transport, metabolism, and growth to promote their survival, reproduction, and virulence. There are 14 classes of GPCRs in fungi involved in sensing various ligands. In this paper, the synthesis of mycotoxins that are GPCR-mediated is discussed with respect to ligands, environmental stimuli, and intra- / interspecific communication. Despite their apparent importance in fungal biology, very little is known about the role of ochratoxin A (OTA) biosynthesis by Aspergillus ochraceus and the ligands that are involved. Fortunately, increasing evidence shows that the GPCR that involves the AF / ST (sterigmatocystin) pathway in fungi belongs to the same genus. Therefore, we speculate that GPCRs play an important role in a variety of environmental signals and downstream pathways in OTA biosynthesis. The verification of this inference will result in a more controllable GPCR target for control of fungal contamination in the future.